Taking stock of nature: Essential biodiversity variables explained. (September 2017) - Brummitt, Neil; Regan, Eugenie C.; Weatherdon, Lauren V.; Martin, Corinne S.; Geijzendorffer, Ilse R.; Rocchini, Duccio; Gavish, Yoni; Haase, Peter; Marsh, Charles J.; Schmeller, Dirk S.
Abstract: In 2013, the Group on Earth Observations Biodiversity Observation Network (GEO BON) developed the framework of Essential Biodiversity Variables (EBVs), inspired by the Essential Climate Variables (ECVs). The EBV framework was developed to distill the complexity of biodiversity into a manageable list of priorities and to bring a more coordinated approach to observing biodiversity on a global scale. However, efforts to address the scientific challenges associated with this task have been hindered by diverse interpretations of the definition of an EBV. Here, the authors define an EBV as a critical biological variable that characterizes an aspect of biodiversity, functioning as the interface between raw data and indicators. This relationship is clarified through a multi-faceted stock market analogy, drawing from relevant examples of biodiversity indicators that use EBVs, such as the Living Planet Index and the UK Spring Index. Through this analogy, the authors seek to make the EBV concept accessible to a wider audience, especially to non-specialists and those in the policy sector, and to more clearly define the roles of EBVs and their relationship with biodiversity indicators. From this we expect to support advancement towards globally coordinated measurements of biodiversity. Highlights: Measuring trends in biodiversity against tractable and achievable conservation goals is difficult. Essential Biodiversity Variables (EBVs) can coordinate biodiversity measurement. Confusion exists regarding the relationship between EBVs and indicators. A stock market analogy is presented as a powerful communication tool. The analogy explains the EBV concept and its relationship to indicators of biodiversity change.